A ‘quiet’ crisis in health care: developing our capacity to hear - Ceci, Christine (Nursing philosophy, 2001)
In this paper we suggest that it is a mistake to understand the current situation in nursing as primarily a problem of ‘shortage’, a problem which may be solved through supplying ‘more nurses, faster’. This way of thinking is understood as reflecting an invalidation of nurses and nursing and, by fostering false beliefs about nursing, as functioning to exacerbate rather than resolve the current situation. Unlike many mainstream conceptualizations of the current situation in nursing, we begin by understanding the experiences and concerns of nurses as meaningful. Feminist and hermeneutic philosophies, as well as Foucauldian perspectives on discourse, encourage us to take seriously the gender relations of power through which nursing comes to be articulated and to cultivate ways of thinking which can generate more productive analyses of the current situation in nursing. Rather than accepting instrumental understandings of nursing as adequate, we question the everyday beliefs and assumptions, the dominant discourses at work both in the world and in ourselves, which allow the suffering of nurses to be thought irrelevant and their concerns to remain unheard. We theorize both why the suffering of nurses can be considered irrelevant in this way and the difference it would make were we to take the experiences of nurses seriously. This undertaking requires that we reflect on that which constrains - and enables - the ways we are able to write, speak and think about nursing.